"Jovens de Projetos": um estudo de caso sobre os jovens do Programa Jovem Aprendiz no município de Vitória/ES. - Mariani, Geovana Cristina de Almeida (2010)
This is a study about young people who participate in Jovem Aprendiz Program, located in Vitória - ES. This research aimed to answer the question: Who are the young participants of the Jovem Aprendiz Program and what their networks of sociability are? To this purpose, we used quantitative and qualitative methodological approaches. We opted for a case study in ethnographic patterns. Some techniques were used for data collection: participant observation; the use of a questionnaire for the participants (both sexes); individual and semi-structured interviews with the technicians and teachers; group interview with young participants, record informal conversations and documents of the Program. The Jovem Aprendiz Program, which appears in the setting of public policy as a policy-oriented for training and placing young people in the labor market, was focused on this research as a place of socialization for young people. The results allow us to consider that the profile of this young people is aged 16 to 17 years, mostly male, mixed race, unmarried, without children, who has studied in high school and belongs to popular class. As for personal and professional expectations, the survey revealed the desire of young people in further study; in postpone marriage, fatherhood and motherhood. This study highlights the importance of sociality for young people in the context of friends, forming groups, the affections, and also in the context of religion and consumption. It was noticed also that participants hid their youth identity in this program, ie, there was no space or time and place for expression or demonstration typically youngs, so there were not understanding and recognition about youth needs and demands in this space. Furthermore, Program’s participants undergo for process of becoming adults sooner. Therefore, we noted two parallel worlds in the same context: the world for young and the world of Program, with its regulations, controls and rules.